Intradiscal Administration of Tumor Necrosis Factor-α Inhibitor, Etanercept, Clinically Improves Intractable Discogenic Low Back Pain. (May 2014) - Sainoh, T.; Orita, S.; Yamauchi, K.; Sakuma, Y.; Kubota, G.; Oikawa, Y.; Inage, K.; Sato, J.; Fujimoto, K.; Takahashi, K.; Ohtori, S.
Introduction: Discogenic low back pain (LBP) has been clinically considered to be one of the sources of intractable LBP. Tumor necrosis factor-α (TNF-α) is one of the well-known pain-related proinflammatory mediators in the degenerative intervertebral disc. However, it is unclear whether its inhibition leads to any analgesic outcomes. In this study, we aimed to examine the effect of intradiscal TNF-α inhibitor administration in discogenic LBP patients. Materials and Methods: Discogenic LBP patients were diagnosed on the basis of physical and radiographic (X-ray and magnetic resonance imaging) findings. Sixty patients were divided randomly into two groups: etanercept group ( n = 30; bupivacaine 2 mL with etanercept 10 mg) and control group ( n = 30; bupivacaine 2 mL). Numerical rating scale score for LBP before and 1 day, 1, 2, and 4 weeks after the injection and Oswestry disability index (ODI) score before and 4 weeks after the injection were evaluated. In addition, complications after the injection were evaluated. Results: While both groups experienced considerable pain relief, the visual analog scale score significantly decreased in the etanercept group at every time point after the injection ( p < 0.05). The ODI score decreased 4 weeks after the injection only in the etanercept group ( p < 0.05). There were no complications in either group. Conclusion: Single intradiscal administration of TNF-α inhibitor showed a greater analgesic effect without any complications lasting for 4 weeks, thereby implying that TNF-α may be profoundly involved in the pathogenesis of chronic discogenic LBP. The present study indicates that intradiscal administration of TNF-α inhibitor can be useful for intractable discogenic LBP treatment in humans. Disclosure of Interest None declared